Kontribusi Jenis Ikan terhadap Nilai Produksi dan Implikasinya terhadap Strategi Pemasaran Perikanan di Perairan Laut Jawa (Studi Kasus Di PPN Muara Angke) - Meutia Mollynda; Fajar Hidayaturohman; Nurul Ekawati (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2025)
The fisheries sector plays a crucial role in supporting food security and coastal economies, particularly in high-intensity fishing areas such as Muara Angke. Drift gillnets are among the dominant fishing gears in the Java Sea, contributing significantly to landings at Muara Angke Fishing Port (PPN Muara Angke). However, the contribution of each fish species to production value and its implications for marketing strategies remain underexplored.This study aims to analyze the contribution of fish species to production value and to identify implications for fisheries marketing strategies in the Java Sea, using secondary data from drift gillnet landings at PPN Muara Angke in 2025. The analysis was conducted by calculating the production volume and value of each species and relating them to market demand and processing potential.The results show that the total drift gillnet production in 2025 reached 35,000 tons, with the largest contributions from skipjack tuna (35.7%), mackerel scad (26.3%), and narrow-barred Spanish mackerel (13.7%). Together, these three species accounted for more than 75% of the total production. The dominance of small to medium pelagic species highlights their economic importance, both for direct consumption and as raw materials for processing industries such as canning, smoking, and freezing. Other species, including scad, round scad, and mixed catches, contributed less but remain essential for catch diversity and local market supply. Marketing strategies should prioritize supply chain strengthening, post-harvest quality improvement, and product diversification for skipjack tuna, mackerel scad, and Spanish mackerel. Meanwhile, minor species can be developed through product differentiation and local marketing to reduce dependency on a few dominant commodities.